Pharyngomalacia in Neonates: The Missed Issue - Moslehi, Mohammad Ashkan (Frontiers in Pediatrics, 2020)
Background: Airway Malacia (AM) is a weakness of the airway’s frameworks making them collapsible during the respiratory phases. Although Larynx, trachea and bronchus are the usual sites for occurring the malacia, there is another important type of malacia that involving the pharynx. Pharyngomalacia (PM) or concentric Pharyngeal Wall Inspiratory Collapse (PWIC) is mostly missed during bronchoscopic evaluations in the neonates with noisy breathing because people are not aware of this condition. Methods: This study aimed to evaluate the nasopharyngeal investigation among neonates suffering from noisy breathing. The retrospective study was undertaken to assess the frequency of PM and to propose indications for intervention in 100 neonates with noisy breathing. The thin size fiberoptic bronchoscope was used to evaluate the upper airways under conscious status without any sedation in the neonates. Results: A total of 100 neonates with noisy breathing from September 2015 to October 2018 were analysed retrospectively. The most common presenting symptom was the inspiratory stridor which was observed in 35 (92.1%) of cases. PM was diagnosed in 38 neonates (38%) including 27(71%) males and 13(29%) females. Seventeen (44.7%) cases had mild, 11 (28.9%) cases had moderate and 10 (26.4%) cases had a severe type of PM. PM was more prominent at velopharynx level in 15 (39.4%) cases and it was accompanied by up to 6 synchronous airway abnormalities. The most frequent synchronous airway abnormality was laryngomalacia 13 (34.3%). Conclusion: PM can be one of the causes of noisy breathing in infants. Since PM can be accompanied by the presence of other types of airways malacia, the issue becomes more complicated. On the other hand, lack of experience and facilities are two main causes for the accurate diagnosis and effective management among the neonates. This study indicates that the investigation of pharynx is a missed part of the many workups that are used to diagnose the site of involvement in the neonates with noisy breathing.